(untitled) (Annals of Medical Research, 2022)
Aim: We aimed to compare the ocular posterior segment parameters in pediatric patients with Familial Mediterranean Fever (FMF) with a healthy control group. Materials and Method: We evaluated 40 pediatric FMF patients and 36 healthy children in this study. Choroidal thicknesses from the subfoveal, nasal and temporal 500 µm, 1000 µm, and 1500 µm points; the subfoveal macular thickness; macular volume; optic nerve head (ONH) parameters; and peripapillary retinal nerve fiber layer (RNFL) thickness were measured. An optical coherence tomography (OCT) device was used for measurements. Results: The choroidal thickness in the temporal 1500 µm was significantly thinner, and average peripapillary RNFL thickness was significantly lower in the FMF group compared to the control group (p=0.015 and p=0.023, respectively). The groups were similar in terms of macular thickness and macular volume. Among the ONH parameters, the rim area thickness was also significantly higher in the FMF group (p= 0.013). Conclusion: This study shows that the recurrent inflammation caused by FMF can affect choroidal thickness and peripapillary RNFL in children.